Ruptured Tubo-Ovarian Pregnancy Presenting at 15 Weeks' Gestation. (31st March 2022) - Keller, Daniel; Morris, Matthew; McLaughlin, Ryan; Evans, David; Joyce, Michael
Abstract : Ectopic pregnancies develop outside of the uterus and lead to significant maternal morbidity and mortality if they rupture. As the primary diagnostic tool for these presentations, ultrasound has a growing list of signs and measurements that help distinguish between intrauterine and ectopic pregnancies, the latter being exceedingly rare once a woman has entered her second trimester. The present case reports a series of Emergency Department visits by a woman carrying a second-trimester pregnancy—deemed intrauterine on transabdominal ultrasound due to gestational age and location—who developed massive hemoperitoneum and was diagnosed with a ruptured 15-week tubo-ovarian pregnancy on laparotomy. The discussion describes the sonographic findings that could have helped make the proper diagnosis, most notably mantle distance—the thickness of the myometrium surrounding the gestational sac—which would have correctly identified this pregnancy as ectopic.